Kinematic stride characteristics of maximal sprint running of elite sprinters - verification of the "Swing-Pull Technique" - Mattes, K.; Wolff, S.; Alizadeh, S. (Journal of Human Kinetics, 2021)
Maximum sprinting speed constitutes an optimum relation between the stride length and the step rate in addition to an appropriate sprinting technique. The kinematics of the sprint step at maximum sprinting speed have already been examined in numerous studies, without reaching a consensus. The aim of this study was to analyze the relationship between maximum sprinting speed and the stride kinematics based on the "Swing-Pull Technique". German elite sprinters (N = 26, body height = 182 ± 6 cm, leg length 93.8 ± 4.1 cm) were tested while performing a 30-meter flying sprint at maximum sprinting speed. The relationship between sprinting speed and kinematic variables was determined via Pearson correlation. Sprinting speed (10.1 - 11.3 m/s) correlated with stride length (r = 0.53), ground contact time (r = -0.53) and variables from the technique model: the knee angle at the end of the knee lift swing (r = 0.40), the maximum knee angle prior to backswing (r = 0.40), the hip extension angle velocity (r = 0.63), and vertical foot velocity (r = 0.77) during pre-support, the ankle angle at the take-on (r = -0.43), knee flexion (r = -0.54), and knee extension (r = -0.47) during support. The results indicate that greater stride length, smaller contact time, and the mentioned kinematic step characteristics are relevant for the production of maximum sprinting speed in athletes at an intermediate to advanced performance level. The association of sprinting speed and these features should primarily be taken into account in conditioning and technical training.